Preparation method of carbon-ceramic brake disc with composite friction layer and carbon-ceramic brake disc
By using the technology of composite friction layer and thermally conductive functional layer in the manufacturing process of carbon ceramic brake discs, the problem of low material utilization is solved, efficient material utilization and excellent braking performance are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411885453.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The low material utilization rate during the manufacturing process of carbon ceramic brake discs leads to an increase in production costs, which restricts its large-scale application.
The carbon ceramic brake disc preparation method with a composite friction layer is adopted to prepare carbon-carbon composite materials by vapor deposition, and rough processing and crushing are carried out to improve material utilization. Then the thermal conduction functional layer and composite friction layer are prepared, and the thermal pressing curing and ceramicization are carried out, and finally the finishing process is carried out.
The raw material utilization rate has been improved from 35%-45% to 75%-80%, reducing production costs, and improving braking performance through thermally conductive functional layer and composite friction layer, reducing noise and jitter, improving heat dissipation performance and thermal fading resistance.
Smart Images

Figure HDA0005199179420000011 
Figure HDA0005199179420000021 
Figure HDA0005199179420000031
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic product and a preparation method thereof, and in particular to a preparation method of a carbon-ceramic brake disc with a composite friction layer and a carbon-ceramic brake disc. Background Art
[0002] As a new generation of high-performance materials, carbon-ceramic composites successfully combine the advantages of carbon-carbon composites and ceramic-based composites. The material has the characteristics of low density, high temperature resistance, long life, and can work stably under high loads and complex environments. It is widely regarded as a highly promising braking material.
[0003] With the growing demand for lightweight electric vehicles and the reduction in manufacturing costs of carbon ceramic brake discs, their applications have gradually expanded from high-end models to new energy vehicles, commercial vehicles and special vehicles. Domestic companies have effectively reduced production costs through technological innovation and large-scale production, making carbon ceramic brake discs increasingly competitive in the market.
[0004] The manufacturing of carbon ceramic brake discs involves the molding of three-dimensional needle-punched preforms, as well as high-precision processes such as chemical vapor infiltration (CVI), precursor infiltration conversion (PIP) and reactive melt infiltration (RMI). However, mechanical processing in these processes inevitably leads to material waste. For example, the material utilization rate of a brake disc with a diameter of 355 mm and a thickness of 28 mm after processing is only 35% to 45%. This low efficiency has greatly increased production costs and restricted its large-scale application. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that the manufacturing process of carbon-ceramic brake disc has low material utilization rate, resulting in increased production costs and restricting its large-scale application, and to provide a method for preparing a carbon-ceramic brake disc with a composite friction layer and a carbon-ceramic brake disc.
[0006] In order to solve the deficiencies of the above-mentioned prior art, the present invention provides the following technical solutions:
[0007] A method for preparing a carbon-ceramic brake disc with a composite friction layer, which is special in that it comprises the following steps:
[0008] Step 1: Deposit a carbon matrix on the three-dimensional needle-punched preform by vapor deposition at a temperature of 600-1200°C to obtain a density of 1.4±0.05g / cm 3 Carbon-carbon composite materials;
[0009] Step 2, processing the carbon-carbon composite material into a carbon-carbon brake disc, and crushing the remaining material in turn to obtain small-sized carbon-carbon composite particles with a diameter of 100-300 μm and large-sized carbon-carbon composite particles with a diameter of 300-500 μm;
[0010] Step 3: prepare a thermal conductive mixture according to a specific mass ratio, wherein the thermal conductive mixture includes an organic resin, a curing agent, a thermal conductive filler, large-sized carbon-carbon composite particles, and an ethanol solution of a silane coupling agent, and hot-press and cure the thermal conductive mixture on the surface of the carbon-carbon brake disc to form a thermal conductive functional layer;
[0011] Step 4, preparing a friction mixture according to a specific mass ratio, the friction mixture comprising an organic resin, a curing agent, a friction filler, small-sized carbon-carbon composite particles, and a silane coupling agent ethanol solution, and hot-pressing and curing the friction mixture on the surface of the carbon-carbon brake disc obtained in step 3 to form a composite friction layer;
[0012] Step 5: Place the carbon-carbon brake disc obtained in step 4 in a high temperature furnace for ceramic treatment at a temperature of 1200-1600°C for 1-4 hours to obtain a density of 2.0-2.8 g / cm 3 Carbon ceramic brake discs;
[0013] Step 6: Finish the carbon-ceramic brake disc, clean up the remaining ceramic raw materials, and perform super-fine grinding on the friction surface to achieve the required surface finish and accuracy, thereby obtaining a carbon-ceramic brake disc with a composite friction layer.
[0014] Furthermore, in step 3, the mass ratios of the organic resin, curing agent, thermally conductive filler, large-size carbon-carbon composite particles, and silane coupling agent ethanol solution are 80-120: 5-20: 20-50: 50-100: 5-10, respectively; the thermally conductive filler is at least one of iron, iron alloy, aluminum, aluminum alloy, copper, copper alloy, alumina, silicon oxide, diatomaceous earth, silicon carbide, boron carbide, mullite, boron nitride, aluminum nitride, and flake carbon.
[0015] Furthermore, in step 4, the mass ratios of the organic resin, the curing agent, the friction filler, the small-sized carbon-carbon composite particles, and the silane coupling agent ethanol solution are 80-120: 5-20: 20-50: 40-80: 4-8 respectively;
[0016] The friction filler is at least one of iron, copper, aluminum oxide, silicon oxide, silicon carbide, lead oxide, asbestos, mullite, graphite, boron nitride, and molybdenum disulfide.
[0017] Furthermore, in step 3, the configuration of the thermal conductive mixture is specifically as follows: firstly, large-sized carbon-carbon composite particles and silane coupling agent ethanol solution are added, and ball milling is performed for 0.5-1h; then, a thermal conductive filler is added, and ball milling is continued for 1-2h; finally, an organic resin and a curing agent are added, and ball milling is performed for 0.5-1h to obtain a thermal conductive mixture;
[0018] In step 4, the friction mixture is specifically configured as follows: first add small-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 0.5-1h; then add friction filler, and continue ball milling for 1-2h; finally add organic resin and curing agent, and ball mill for 0.5-1h to obtain the friction mixture.
[0019] Furthermore, in step 3 and step 4, the organic resin is furan resin or phenolic resin, the curing agent is xylene sulfonic acid or urotropine, and the solute of the silane coupling agent ethanol solution is one of aminosilane, mercaptosilane, and methylvinylsilane, with a mass fraction of 1%.
[0020] Furthermore, in step 3 and step 4, the hot pressing pressure of the hot pressing curing is 1-5 MPa, the curing temperature is 150-200° C., and the curing time is 1-3 h;
[0021] In step 3, the thickness of the thermal conductive functional layer is 1-3 mm;
[0022] In step 4, the thickness of the composite friction layer is 1-2 mm.
[0023] Furthermore, in step 5, the ceramic raw material for the ceramic treatment is selected from at least one of silicon powder, iron powder, copper powder, ferrosilicon alloy powder, and copper-iron alloy powder.
[0024] At the same time, the present invention also provides a carbon-ceramic brake disc with a composite friction layer, which is special in that it is prepared by adopting the above-mentioned method for preparing a carbon-ceramic brake disc with a composite friction layer.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention provides a method for preparing a carbon-ceramic brake disc with a composite friction layer, which comprises the following steps in sequence: preparation of a carbon-carbon composite material, rough machining, preparation of a heat conductive functional layer, preparation of a composite friction layer, ceramic treatment, and fine machining; wherein the rough machining is to crush the residual material produced during the machining process as a raw material for subsequent steps to improve the utilization rate of raw materials and reduce production costs. Taking the machining of a φ355*28mm brake disc as an example, the utilization rate of raw materials after conventional machining is only 35%-45%; while the utilization rate of raw materials of the present invention is as high as 75%-80%; and the heat conductive functional layer can effectively reduce the disc surface temperature during braking and extend the life of surrounding accessories such as calipers. The components of the composite friction layer are uniform and can be designed to reduce noise and vibration during braking.
[0027] (2) The carbon ceramic brake disc with a composite friction layer of the present invention combines the advantages of a three-dimensional needle-punched structure and a molded structure. The middle bearing layer adopts a three-dimensional needle-punched preform, and the brake disc has better mechanical properties, ensuring the safety and reliability of the connection. The composite friction layer is prepared by a molding process, sacrificing some mechanical properties in exchange for more stable friction braking performance. Moreover, adding the functional powder by molding is simpler than adding it inside the three-dimensional needle-punched preform, and the processability is better.
[0028] (3) The carbon-ceramic brake disc with a composite friction layer of the present invention has a significantly lower end value of the brake temperature of the brake disc in the characteristic value stage, and the temperature rise of the brake temperature curve of the brake disc in the thermal decay stage becomes slower, indicating that the present invention has excellent heat dissipation performance and stronger resistance to thermal decay. It can still maintain good friction performance and pressure stability in the high temperature stage, and is suitable for long-term high-frequency braking scenarios.
[0029] (4) In the carbon-ceramic brake disc with a composite friction layer of the present invention, the composite friction layer prepared by a hot pressing process has uniform components, can be designed according to requirements, and has good braking stability; while the existing carbon-ceramic brake discs usually use a three-dimensional needle-punched preform, and there is a difference in the component proportions of the mesh tire layer and the non-woven fabric layer. During the friction process, the mesh tire and the non-woven fabric layer are prone to alternate friction, causing more obvious noise and vibration. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the test results of the friction coefficient change (blue) and the brake temperature change (red) of the experimental group at the characteristic value 1 stage in Example 1 of the method for preparing a carbon-ceramic brake disc with a composite friction layer of the present invention;
[0031] Figure 2 It is a schematic diagram of the test results of the friction coefficient change (blue) and the brake disc brake temperature change (red) of the control group in the characteristic value stage 1 in Example 1 of the present invention;
[0032] Figure 3 It is a schematic diagram of the test results of the friction coefficient change (blue) and the brake disc brake temperature change (red) of the experimental group in the characteristic value 2 stage in Example 1 of the present invention;
[0033] Figure 4 It is a schematic diagram of the test results of the friction coefficient change (blue) and the brake disc brake temperature change (red) of the control group in the characteristic value stage 2 in Example 1 of the present invention;
[0034] Figure 5 It is a schematic diagram of the test results of the friction coefficient change (blue) and the brake disc brake temperature change (red) of the experimental group in the characteristic value stage 3 in Example 1 of the present invention;
[0035] Figure 6It is a schematic diagram of the test results of the friction coefficient change (blue) and the brake disc brake temperature change (red) of the control group in the characteristic value stage 3 in Example 1 of the present invention;
[0036] Figure 7 It is a schematic diagram of the test results of the friction coefficient change (blue), brake disc brake temperature change (red), and piston pressure value change (green) of the experimental group in the first embodiment of the present invention at the thermal decay stage 1;
[0037] Figure 8 Schematic diagram of the test results of the change in friction coefficient (blue), brake disc brake temperature (red), and piston pressure value (green) of the control group in the first embodiment of the present invention during the thermal decay stage 1. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings and exemplary embodiments.
[0039] Embodiment 1
[0040] A method for preparing a carbon-ceramic brake disc with a composite friction layer comprises the following steps:
[0041] Step 1, preparing carbon-carbon composite material;
[0042] The carbon matrix was deposited on the three-dimensional needle-punched preform by vapor deposition at a temperature of 950°C to obtain a density of 1.4 g / cm 3 Carbon-carbon composite materials;
[0043] The deposition temperature can be set to a minimum of 600°C and a maximum of 1200°C; the density of the carbon-carbon composite material can be 1.4±0.05g / cm 3 , to provide a moderate porosity, which is conducive to the carbon-ceramic brake disc with a composite friction layer to find a good balance between mechanical properties, composite layer bonding strength and ceramic efficiency, ensuring the lightweight, high performance and durability of the brake disc;
[0044] The carbon source gas used for deposition is liquefied petroleum gas, and the carrier gas used is argon;
[0045] Step 2, rough processing;
[0046] The carbon-carbon composite material is processed into a carbon-carbon brake disc, and the residual material is crushed in turn to obtain small-sized carbon-carbon composite particles with a diameter of 100-300 μm and large-sized carbon-carbon composite particles with a diameter of 300-500 μm; step 2 reduces waste by recycling materials, and provides two sizes of carbon-carbon composite particles for subsequent preparation of composite friction layers, which play a role in toughening and strengthening, help improve the overall performance of the composite layer, and improve material utilization;
[0047] Step 2.1, processing the carbon-carbon composite material into a carbon-carbon brake disc according to the designed size, wherein the carbon-carbon brake disc is provided with a ventilation groove, a connecting flange and a mounting hole;
[0048] Step 2.2, retain the middle circular material head and four corner material heads, and grind them into 100 μm-500 μm by coarse grinding, medium grinding and fine grinding, and sieve them into small-sized carbon-carbon composite particles with a diameter of 100-300 μm and large-sized carbon-carbon composite particles with a diameter of 300-500 μm;
[0049] Step 3: Preparation of thermal conductive functional layer;
[0050] A thermal conductive mixture is prepared according to a specific mass ratio, wherein the thermal conductive mixture includes an organic resin, a curing agent, a thermal conductive filler, large-sized carbon-carbon composite particles, and an ethanol solution of a silane coupling agent, and the thermal conductive mixture is hot-pressed and cured on the surface of a carbon-carbon brake disc to form a thermal conductive functional layer;
[0051] The mass ratios of organic resin, curing agent, thermal conductive filler, large-sized carbon-carbon composite particles, and silane coupling agent ethanol solution are 80-120: 5-20: 20-50: 50-100: 5-10 respectively; the organic resin and curing agent synergistically provide a matrix framework and form a solid structure through a cross-linking reaction; the synergistic effect of the thermal conductive filler and the large-sized carbon-carbon particles forms an efficient heat conduction path, which significantly improves the heat dissipation capacity of the thermal conductive functional layer; the combination of organic resin and carbon-carbon particles enhances the structural strength and ensures the stability and durability of the thermal conductive functional layer under high temperature and high load; the chemical bond between the silane coupling agent and the particle surface reduces the risk of interlayer separation and ensures the firm bonding of the thermal conductive functional layer and the carbon-carbon brake disc; the uniformity of the distribution of the resin matrix and the carbon-carbon particles effectively disperses stress, reduces the generation of cracks during thermal cycling, and prolongs the service life; the above synergistic effect provides a guarantee for the stable operation of the brake disc under high temperature and high load conditions;
[0052] Step 3.1, weighing organic resin, curing agent, thermal conductive filler, large-sized carbon-carbon composite particles, and silane coupling agent ethanol solution respectively in a mass ratio of 100:8:45:70:7;
[0053] Among them, the organic resin is phenolic resin, the curing agent is urotropine, the solute of the silane coupling agent ethanol solution is aminopropyl triethoxysilane, and the mass fraction is 1%; the thermal conductive filler is a mixture of copper powder, mullite, diatomaceous earth, aluminum nitride, and flake carbon powder in a mass ratio of 7:15:13:5:5; in other embodiments, the solute of the silane coupling agent ethanol solution can also be one of alcohol silane and methyl vinyl silane; the thermal conductive filler can also be iron, iron alloy, aluminum, aluminum alloy, copper, copper alloy, aluminum oxide, silicon oxide, diatomaceous earth, silicon carbide, boron carbide, mullite, boron nitride, aluminum nitride, and flake carbon at least one;
[0054] Step 3.2, first add large-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 0.5h; then add thermal conductive filler, and continue ball milling for 1.5h; finally add organic resin and curing agent, and ball mill for 1h to obtain a thermal conductive mixture;
[0055] Step 3.3, hot pressing and curing the thermal conductive mixture on the surface of the carbon-carbon brake disc to form a thermal conductive functional layer with a thickness of 2 mm;
[0056] The hot pressing pressure is 3MPa, the curing temperature is 200℃, and the curing time is 1h. Hot pressing promotes the formation of a continuous thermal conductive network inside the material, greatly improves the heat dissipation efficiency of the thermal conductive functional layer, and reduces the accumulation of brake heat. The thermal conductive functional layer after hot pressing provides a basis for the composite friction layer, improves the bonding force between the composite friction layer and the carbon-carbon brake disc, and extends the life of the carbon-ceramic brake disc with a composite friction layer. In addition, hot pressing reduces porosity, improves the thermal fatigue resistance and thermal cycle stability of the thermal conductive functional layer, and ensures that the carbon-ceramic brake disc with a composite friction layer has reliable performance in a high temperature environment.
[0057] Step 4: preparing the composite friction layer;
[0058] A friction mixture is prepared according to a specific mass ratio, wherein the friction mixture includes an organic resin, a curing agent, a friction filler, small-sized carbon-carbon composite particles, and an ethanol solution of a silane coupling agent. The friction mixture is hot-pressed and cured on the surface of the carbon-carbon brake disc obtained in step 3 to form a composite friction layer; wherein the mass ratios of the organic resin, the curing agent, the friction filler, the small-sized carbon-carbon composite particles, and the ethanol solution of the silane coupling agent are 80-120: 5-20: 20-50: 40-80: 4-8 respectively; the small-sized carbon-carbon composite particles improve the mechanical properties and friction properties, and they work together with the friction filler to reduce heat accumulation during braking, and they are combined with the organic resin to ensure the structural uniformity and stability of the composite friction layer; the silane coupling agent is used to improve the interface bonding between the small-sized carbon-carbon composite particles, the friction filler and the organic resin:
[0059] Step 4.1, weighing organic resin, curing agent, friction filler, small-sized carbon-carbon composite particles, and silane coupling agent ethanol solution respectively in a mass ratio of 100:8:40:60:6;
[0060] The organic resin is phenolic resin, the curing agent is hexamethylenetetramine, the solute of the silane coupling agent ethanol solution is aminopropyltriethoxysilane, and the mass fraction is 1%; the friction filler is a mixture of copper powder, mullite, silicon carbide, and molybdenum disulfide in a mass ratio of 5:17:10:8; in other embodiments, the solute of the silane coupling agent ethanol solution can also be one of alcohol silane and methyl vinyl silane; the friction filler can be at least one of iron, copper, aluminum oxide, silicon oxide, silicon carbide, lead oxide, asbestos, mullite, graphite, boron nitride, and molybdenum disulfide;
[0061] Step 4.2, first add small-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 0.5h; then add friction filler, and continue ball milling for 1h; finally add organic resin and curing agent, and ball mill for 0.5h to obtain friction mixture;
[0062] Step 4.3, hot-pressing and curing the friction mixture on the surface of the carbon-carbon brake disc obtained in step 3 to form a composite friction layer with a thickness of 2 mm;
[0063] Among them, the hot pressing pressure is 3MPa, the curing temperature is 200°C, and the curing time is 1h; the hot pressing pressure and curing temperature increase the reaction rate, ensure the density of the composite friction layer, and the hot pressing pressure promotes the close combination of particles and the matrix, reduces the porosity, and enhances the strength and heat resistance of the composite friction layer;
[0064] Step 5: Ceramic treatment;
[0065] The carbon-carbon brake disc obtained in step 4 was placed in a high-temperature furnace for ceramic treatment at a temperature of 1600°C for 2 hours to obtain a density of 2.0 g / cm 3 Carbon ceramic brake discs;
[0066] The ceramic raw material for the ceramic treatment is silicon powder; in other embodiments, the ceramic raw material can be at least one of silicon powder, iron powder, copper powder, ferrosilicon alloy powder, and copper-iron alloy powder;
[0067] Step 6: Finishing;
[0068] The carbon-ceramic brake disc is finely processed, the residual ceramic raw materials at the connecting flange and the mounting hole are cleaned, and the friction surface is ultra-finely ground to achieve the required surface finish and accuracy, thereby obtaining a carbon-ceramic brake disc with a composite friction layer.
[0069] The test was conducted according to SAE J2522-2014 "Recommended Method for Global Braking Performance Bench Test of Ground Vehicles", with a four-piston caliper and a PAGID-RSC1 grinding disc; the carbon-ceramic brake disc with a composite friction layer obtained in Example 1 was used as an experimental group, and the carbon-ceramic brake disc without a friction layer prepared in steps 1, 2, 5, and 6 of this example was used as a control group;
[0070] Figure 1 , Figure 2The schematic diagram of the test results of the friction coefficient change (blue) and brake disc brake temperature change (red) of the experimental group and the control group in the characteristic value 1 stage, respectively. The brake pressure is 30 bar, the speed range is 80-30 km / h, indicating that the friction performance is measured during deceleration. The starting temperature is 100 ° C. The horizontal axis is the number of brake applications (No. of Brake Appl.), that is, the number of brake cycles performed during the test; the average friction coefficient (Avg.μ) is 0.41; comparison Figure 1 , Figure 2 In each deceleration cycle, the friction coefficient and brake disc temperature fluctuation range of the experimental group are smaller, indicating that its friction stability and thermal stability are better than those of the control group.
[0071] Figure 3 , Figure 4 Schematic diagrams of the test results of friction coefficient change and brake disc brake temperature change in the experimental group and the control group in the characteristic value stage 2, respectively. The braking pressure is 30 bar, the speed range is 80-30 km / h, and the friction performance is measured during deceleration. The starting temperature is 100°C. The average friction coefficients of the experimental group and the control group are 0.42 and 0.48, respectively. The control group has a higher initial friction coefficient in the characteristic value stage 2, but this sacrifices other properties (such as durability or resistance to thermal decay). The friction coefficient curve of the experimental group is relatively stable with a smaller fluctuation range, showing better friction stability, and the brake disc temperature changes smoothly throughout the braking process without large fluctuations.
[0072] Figure 5 , Figure 6 The schematic diagrams show the test results of the friction coefficient change and brake disc brake temperature change of the experimental group and the control group in the characteristic value stage 3, respectively. The braking pressure is 30 bar, the speed range is 80-30 km / h, and the friction performance is measured during deceleration. The starting temperature is 100°C. The average friction coefficients of the experimental group and the control group are 0.38 and 0.44, respectively. The experimental group shows higher consistency in friction performance, which is suitable for application scenarios that require continuous high stability, and has better heat dissipation performance, which can delay the occurrence of thermal decay.
[0073] Figure 7 , Figure 8Schematic diagram of the test results of the change in friction coefficient, brake disc brake temperature, and piston pressure value (green) of the experimental group and the control group in the first stage of thermal decay, respectively. The initial temperature condition (T(I)) is 550°C, the deceleration (a) is 0.4g, and the speed range is from 100km / h to 5km / h. The average friction coefficients of the experimental group and the control group are 0.41 and 0.44, respectively, and the minimum friction coefficients of the experimental group and the control group are 0.38 and 0.32, respectively. The friction coefficient of the experimental group is more stable, the heat dissipation performance is excellent, and the thermal decay resistance is stronger. It can still maintain good friction performance and pressure stability in the high temperature stage, which is suitable for long-term high-frequency braking scenarios.
[0074] Embodiment 2
[0075] A method for preparing a carbon-ceramic brake disc with a composite friction layer comprises the following steps:
[0076] Step 1, preparing carbon-carbon composite material;
[0077] The carbon matrix was deposited on the three-dimensional needle-punched preform by vapor deposition at a temperature of 800°C to obtain a density of 1.35 g / cm 3 Carbon-carbon composite materials;
[0078] The carbon source gas used for deposition is liquefied petroleum gas, and the carrier gas used is nitrogen;
[0079] Step 2, same as in Example 1;
[0080] Step 3: Preparation of thermal conductive functional layer;
[0081] Step 3.1, weighing organic resin, curing agent, thermal conductive filler, large-sized carbon-carbon composite particles, and silane coupling agent ethanol solution respectively in a mass ratio of 80:8:25:60:6;
[0082] The organic resin is furan resin, the curing agent is xylene sulfonic acid, and the solute of the silane coupling agent ethanol solution is phenylaminopropyltrimethoxysilane, with a mass fraction of 1%;
[0083] The thermal conductive filler is a metal powder and a non-metal powder, specifically a mixture of iron powder, aluminum oxide, silicon oxide, and flake carbon powder in a mass ratio of 8:8:4:5;
[0084] Step 3.2, first add large-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 0.5h; then add thermal conductive filler, and continue ball milling for 1h; finally add organic resin and curing agent, and ball mill for 1h to obtain a thermal conductive mixture;
[0085] Step 3.3, hot pressing and curing the thermal conductive mixture on the surface of the carbon-carbon brake disc to form a thermal conductive functional layer with a thickness of 3 mm;
[0086] Among them, the hot pressing pressure is 4MPa, the curing temperature is 200℃, and the curing time is 2h;
[0087] Step 4: preparing the composite friction layer;
[0088] Step 4.1, weighing organic resin, curing agent, friction filler, small-sized carbon-carbon composite particles, and silane coupling agent ethanol solution respectively in a mass ratio of 80:8:35:50:5;
[0089] The organic resin is phenolic resin, the curing agent is hexamethylenetetramine, and the solute of the silane coupling agent ethanol solution is aminopropyltriethoxysilane, with a mass fraction of 1%;
[0090] The friction filler is a mixture of metal powder and non-metal powder, specifically a mixture of iron powder, silicon carbide, lead oxide, mullite and graphite in a mass ratio of 5:12:7:10:8;
[0091] Step 4.2, first add small-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 0.5h; then add friction filler, and continue ball milling for 1h; finally add organic resin and curing agent, and ball mill for 1h to obtain friction mixture;
[0092] Step 4.3, hot-pressing and curing the friction mixture on the surface of the carbon-carbon brake disc obtained in step 3 to form a composite friction layer with a thickness of 2 mm;
[0093] Among them, the hot pressing pressure is 4MPa, the curing temperature is 200℃, and the curing time is 2h;
[0094] Step 5: Ceramic treatment;
[0095] The carbon-carbon brake disc obtained in step 4 was placed in a high-temperature furnace for ceramic treatment at a temperature of 1500°C for 3 hours to obtain a density of 2.1 g / cm 3 Carbon ceramic brake discs;
[0096] The ceramic raw material for ceramic treatment is silicon powder;
[0097] Step 6: Same as in Example 1.
[0098] Embodiment 3
[0099] A method for preparing a carbon-ceramic brake disc with a composite friction layer comprises the following steps:
[0100] Step 1, preparing carbon-carbon composite material;
[0101] The carbon matrix was deposited on the three-dimensional needle-punched preform by vapor deposition at a temperature of 1050°C to obtain a density of 1.45 g / cm 3 Carbon-carbon composite materials;
[0102] The carbon source gas used for deposition is natural gas, and the carrier gas used is argon;
[0103] Step 2, same as in Example 1;
[0104] Step 3: Preparation of thermal conductive functional layer;
[0105] Step 3.1, weighing organic resin, curing agent, thermal conductive filler, large-sized carbon-carbon composite particles, and silane coupling agent ethanol solution respectively in a mass ratio of 120:20:35:90:9;
[0106] The organic resin is furan resin, the curing agent is xylene sulfonic acid, and the solute of the silane coupling agent ethanol solution is phenylaminopropyltrimethoxysilane, with a mass fraction of 1%;
[0107] The thermal conductive filler is a mixture of aluminum nitride, aluminum oxide, diatomaceous earth, boron carbide and flake carbon powder in a mass ratio of 6:7:7:10:5;
[0108] Step 3.2, first add large-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 1 hour; then add thermal conductive filler, and continue ball milling for 2 hours; finally add organic resin and curing agent, and ball mill for 1 hour to obtain a thermal conductive mixture;
[0109] Step 3.3, hot pressing and curing the thermal conductive mixture on the surface of the carbon-carbon brake disc to form a thermal conductive functional layer with a thickness of 2 mm;
[0110] Among them, the hot pressing pressure is 2MPa, the curing temperature is 150℃, and the curing time is 3h;
[0111] Step 4: preparing the composite friction layer;
[0112] Step 4.1, weighing organic resin, curing agent, friction filler, small-sized carbon-carbon composite particles, and silane coupling agent ethanol solution respectively in a mass ratio of 120:20:40:70:7;
[0113] The organic resin is phenolic resin, the curing agent is hexamethylenetetramine, and the solute of the silane coupling agent ethanol solution is aminopropyltriethoxysilane, with a mass fraction of 1%;
[0114] The friction filler is a mixture of silicon carbide, mullite, asbestos, graphite and boron nitride in a mass ratio of 7:12:10:8:3;
[0115] Step 4.2, first add small-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 1 hour; then add friction filler, and continue ball milling for 2 hours; finally add organic resin and curing agent, and ball mill for 1 hour to obtain friction mixture;
[0116] Step 4.3, hot-pressing and curing the friction mixture on the surface of the carbon-carbon brake disc obtained in step 3 to form a composite friction layer with a thickness of 1 mm;
[0117] Among them, the hot pressing pressure is 2MPa, the curing temperature is 150℃, and the curing time is 3h;
[0118] Step 5: Ceramic treatment;
[0119] The carbon-carbon brake disc obtained in step 4 was placed in a high-temperature furnace for ceramic treatment at a temperature of 1400°C for 3 hours to obtain a density of 2.4 g / cm 3 Carbon ceramic brake discs;
[0120] The ceramic raw materials used in the ceramic treatment are silicon powder and ferrosilicon alloy powder;
[0121] Step 6: Same as in Example 1.
Claims
1. A method for preparing a carbon ceramic brake disc with a composite friction layer, characterized in that: The steps include: Step 1: Deposit a carbon matrix on the three-dimensional needle-punched preform by vapor deposition at a temperature of 600-1200°C to obtain a density of 1.4±0.05g / cm 3 Carbon-carbon composite materials; Step 2, processing the carbon-carbon composite material into a carbon-carbon brake disc, and crushing the remaining material in turn to obtain small-sized carbon-carbon composite particles with a diameter of 100-300 μm and large-sized carbon-carbon composite particles with a diameter of 300-500 μm; Step 3: prepare a thermal conductive mixture according to a specific mass ratio, wherein the thermal conductive mixture includes an organic resin, a curing agent, a thermal conductive filler, large-sized carbon-carbon composite particles, and an ethanol solution of a silane coupling agent, and hot-press and cure the thermal conductive mixture on the surface of the carbon-carbon brake disc to form a thermal conductive functional layer; Step 4, preparing a friction mixture according to a specific mass ratio, the friction mixture comprising an organic resin, a curing agent, a friction filler, small-sized carbon-carbon composite particles, and a silane coupling agent ethanol solution, and hot-pressing and curing the friction mixture on the surface of the carbon-carbon brake disc obtained in step 3 to form a composite friction layer; Step 5: Place the carbon-carbon brake disc obtained in step 4 in a high temperature furnace for ceramic treatment at a temperature of 1200-1600°C for 1-4 hours to obtain a density of 2.0-2.8 g / cm 3 Carbon ceramic brake discs; Step 6: Finish the carbon-ceramic brake disc, clean up the remaining ceramic raw materials, and perform super-fine grinding on the friction surface to achieve the required surface finish and accuracy, thereby obtaining a carbon-ceramic brake disc with a composite friction layer.
2. The method for preparing a carbon-ceramic brake disc with a composite friction layer according to claim 1, characterized in that: In step 3, the mass ratios of the organic resin, curing agent, thermal conductive filler, large-size carbon-carbon composite particles, and silane coupling agent ethanol solution are 80-120:5-20:20-50:50-100:5-10 respectively; the thermal conductive filler is at least one of iron, iron alloy, aluminum, aluminum alloy, copper, copper alloy, alumina, silicon oxide, diatomaceous earth, silicon carbide, boron carbide, mullite, boron nitride, aluminum nitride, and flake carbon.
3. The method for preparing a carbon-ceramic brake disc with a composite friction layer according to claim 2, characterized in that: In step 4, the mass ratios of the organic resin, curing agent, friction filler, small-sized carbon-carbon composite particles, and silane coupling agent ethanol solution are 80-120:5-20:20-50:40-80:4-8 respectively; The friction filler is at least one of iron, copper, aluminum oxide, silicon oxide, silicon carbide, lead oxide, asbestos, mullite, graphite, boron nitride, and molybdenum disulfide.
4. The method for preparing a carbon-ceramic brake disc with a composite friction layer according to claim 3, characterized in that: In step 3, the configuration of the thermal conductive mixture is specifically as follows: firstly, large-sized carbon-carbon composite particles and silane coupling agent ethanol solution are added, and ball milling is performed for 0.5-1h; then, a thermal conductive filler is added, and ball milling is continued for 1-2h; finally, an organic resin and a curing agent are added, and ball milling is performed for 0.5-1h to obtain a thermal conductive mixture; In step 4, the friction mixture is specifically configured as follows: first add small-sized carbon-carbon composite particles and silane coupling agent ethanol solution, and ball mill for 0.5-1h; then add friction filler, and continue ball milling for 1-2h; finally add organic resin and curing agent, and ball mill for 0.5-1h to obtain the friction mixture.
5. The method for preparing a carbon-ceramic brake disc with a composite friction layer according to claim 1, characterized in that: In step 3 and step 4, the organic resin is furan resin or phenolic resin, the curing agent is xylene sulfonic acid or urotropine, and the solute of the silane coupling agent ethanol solution is one of aminosilane, mercaptosilane, and methylvinylsilane, with a mass fraction of 1%.
6. A method for preparing a carbon-ceramic brake disc with a composite friction layer according to any one of claims 1 to 5, characterized in that: In step 3 and step 4, the hot pressing pressure of the hot pressing curing is 1-5 MPa, the curing temperature is 150-200° C., and the curing time is 1-3 h; In step 3, the thickness of the thermal conductive functional layer is 1-3 mm; In step 4, the thickness of the composite friction layer is 1-2 mm.
7. The method for preparing a carbon-ceramic brake disc with a composite friction layer according to claim 6, characterized in that: In step 5, the ceramic raw material for the ceramic treatment is selected from at least one of silicon powder, iron powder, copper powder, ferrosilicon alloy powder, and copper-iron alloy powder.
8. A carbon-ceramic brake disc with a composite friction layer, characterized in that: The carbon-ceramic brake disc with a composite friction layer is prepared by the preparation method of claim 1.
Citation Information
Patent Citations
Carbon-ceramic composite brake disc and preparation method thereof
CN103553695A
Brake block for disc brake
CN106810816A
Preparation technology of C / C-SiC ventilation brake disc with silicon carbide friction functional layer
CN108299002A
Carbon-ceramic brake disc with wear-resistant coating and preparation method of carbon-ceramic brake disc
CN118459248A
Carbon-ceramic brake disc with double friction layers and preparation method of carbon-ceramic brake disc
CN119042255A
Cited By
Aluminum silicon carbide brake disc based on pressure infiltration process and preparation method thereof
CN120662790A
High-thermal-conductivity light-weight composite friction material and warm-pressing forming process thereof
CN122500872A